Implementasi Pengenalan Bahasa Bima Dalam Menstimulasi Perkembangan Literasi Budaya Pada Anak Usia 5-6 Tahun di TK Tunas Mulia - Julaiha Julaiha; Hendra Hendra; Sri Wahyuningsih (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to describe the implementation of Bima language introduction in stimulating cultural literacy among children aged 5–6 years at Tunas Mulia Kindergarten, Sambori Village, Bima Regency. This research employed a qualitative approach using a case study design. The research subjects consisted of one classroom teacher, one principal, and 12 children from Group B. Data were collected through participatory observation, semi-structured interviews, and documentation, and were then analyzed using the Miles and Huberman interactive model. The findings indicate that the introduction of the Bima language was implemented through three main methods: habituation through bilingual instructions, storytelling activities using traditional Bima folktales, and cultural literacy stimulation through the introduction of cultural vocabulary, understanding of cultural values, and the development of pride in local culture. The obstacles encountered in its implementation included limited Bima language-based learning media, insufficient exposure to the local language in the family environment, differences in children’s initial abilities, and limited references and teacher training. This study emphasizes that teachers’ roles and environmental support are essential in integrating local languages as an effort to strengthen children’s cultural literacy from an early age.